Credit Ratings and Capital Structure in Chinese Listed Companies - WANG, QIAN (2017)
Abstract This paper examines to what extent credit ratings affect capital structure decisions in Chinese listed companies. The data sample contains 2486 Chinese non-financial companies listed on A-share of Shanghai and Shenzhen Stock Exchange (excluding companies listed in the growth enterprise market) in the period 2010 to 2016. Three considerations about credit ratings are investigated. The author first concentrates on the effect of accessing to the Chinese bond market on firm’ s leverage, which is measured by having credit ratings. Secondly, the author is interested in how being near a change of rating level affects leverage adjustment. The final one identifies how firms will change their capital structure after an upgrade or downgrade in credit ratings. The test models include credit rating proxies aiming to capture the credit rating effects on capital structure. Overall, the author finds firms are expected to be affected by credit ratings when they make decisions about capital structure. Firms participating into bond market are more likely to have higher leverage than other firms. Firms tend to change their leverage once there is a potential change in credit rating, and this affects more on firms near a downgrade of ratings. Concerning about the change in credit ratings, the author finds firms experiencing a downgrade in credit ratings will reduce leverage while it is not significant for upgrade firms adjusting their capital structure. The author concludes that firms concern about the credit ratings when they determine their capital structure. In general, the finds are consisted with previous empirical studies in developed countries.